Equipping Teachers and Staff with General English Skills: A Community Service - Widiningrum, Rindang; Murtisari, Elisabet Titik; Hastuti, Gita; Aichi, Nisrina; Anggraeny, Mutiara Elok (Jurnal Abdimas, 2025)
In today's globalized world, school teachers and staff need to equip themselves with English skills not only for the classroom but also for broader communication. This community service program aimed to improve their general English competence for daily interactions by involving teachers and administrative staff of a private elementary school in Salatiga. The program began with a needs analysis through interviews to identify their English language needs. Based on these findings, the materials were designed and delivered using learner-centered methods. The training was conducted over five sessions, each lasting about 100 minutes, and incorporated technology to enhance engagement. As a result of the training, the participants reported positive benefits for their daily activities at school.